Chronic consumption of thermally processed palm oil or canola oil modified gut microflora of rats - Mengcheng Ruan; Yiran Bu; Fangjie Wu; Shijie Zhang; Rulong Chen; Na Li; Zhiguo Liu; Hualin Wang (Food Science and Human Wellness)
Dietary oils have critical influences on human health, and thermally cooking or frying modify the components and nutritional functions of oils. Palm oil was the most widely used oil in food processing industry, but its health effects remain debatable. In the current study, we aimed to compare the effects of thermally oxidized palm oil and canola oil on gut microbiota. Palm oil or canola oil were heated at 180 °C for 10 h to prepare high-fat diets. Rats were fed high-fat diets for 3 months, and hematological properties, gut microflora composition and intestinal gene expression were examined. The results indicated that heated canola oil consumption elevated plasma total cholesterol and LDL-c levels compared with unheated canola oil, but heated palm oil do not had these effects; and consumption of heated palm oil significantly elevated the relative abundance of Lactobacillucs and Roseburia in gut, compared with non-heated palm oil or two canola oil groups. Moreover, intestinal expression of IL-22 was increased in heated palm oil fed animal, though ZO-1 and GPR41 were reduced. In conclusion, heating process may enhance the effects of palm oil on proliferation of probiotics Lactobacillucs, and weaken the effects of canola oil on cholesterol transport and metabolism.